Porous Fibers: Controlled Design of a Robust Hierarchically Porous and Hollow Carbon Fiber Textile for High‐Performance Freestanding Electrodes (Adv. Sci. 21/2019). Issue 21 (8th November 2019) - Li, Quanxiang; Wang, Jiemin; Liu, Chao; Fakhrhoseini, Seyed Mousa; Liu, Dan; Zhang, Liangzhu; Lei, Weiwei; Naebe, Minoo
Abstract : In article number 1900762, Weiwei Lei, Minoo Naebe, and co‐workers propose an inventive "dynamic template calcination" strategy to construct hierarchical macro–meso–microporous and hollow carbon fiber textile system without diminishing mechanical robustness. Such unique characteristics offer high surface area and minimized diffusive resistance to mass transport, resulting in a flexible and efficient freestanding electrode.